Role of radiotherapy in improving activity of immune-modulating drugs in advanced renal cancer: Biological rationale and clinical evidences. (September 2018) - Buttigliero, Consuelo; Allis, Simona; Tucci, Marcello; Zichi, Clizia; Leone, Gianmarco; Di Stefano, Rosario Francesco; Ruo Redda, Maria Grazia; Ricardi, Umberto; Scagliotti, Giorgio Vittorio; Di Maio, Massimo; Filippi, Andrea Riccardo
Highlights: Immune checkpoint inhibitors have been widely investigated and led to remarkable results in RCC. Radiotherapy-induced cell death leads to release of cytokines that stimulate immune response. Disease control increase when radiotherapy is combined with checkpoint inhibitors. Several trials are ongoing testing the activity of radiotherapy combined to immune-modulating agents. Abstract: In the last few years, immune checkpoint inhibitors have been extensively investigated in renal cell carcinoma and led to remarkable results. Radiation therapy may increase the activity of immune modulating agents through different mechanisms, priming the immune system, recruiting immune cells to the tumor environment, and altering the immunosuppressive effects of the tumor microenvironment. Preclinical studies reported increased loco-regional control when radiation is combined with immune-checkpoint blockade. Moreover, increased systemic disease control has been demonstrated when local radiation is combined with both anti-CTLA-4 and anti-PD-1/PD-L1 inhibitors. Actually, several trials are ongoing testing the activity of radiation therapy in combination with different immune-modulating agents for the treatment of metastatic renal cell carcinoma. The aim of this paper is to focus on the biological rationale of adding radiation therapy to immune-modulating agents in renal cell carcinoma and to review the currently available clinical evidence about the combination of radiotherapy and immunotherapy.